Forest digital twin as a relaxation environment: A pilot study - Hejtmánek, Lukáš; Hůla, Martin; Herrová, Anna; Surový, Peter (Frontiers in Virtual Reality, 2022)
Forest environments have been proven beneficial for physiological well-being, supporting relaxation and meditative processes. Unfortunately, some groups, predominantly those with reduced mobility, are prevented from forest visitation. Presenting such environments in virtual reality could provide a viable substitute. However, as forest structure and composition are important aspects of its restorative power, to accurately compare the efficacy of virtual forests to that of real natural spaces, the virtual environment should match the real location as closely as possible. Furthermore, if participants achieve similar benefits in both settings, virtual copies (digital twins) of forests could be a viable option for studying forest bathing in a controlled environment. We collected LiDAR scans of a forest location near Prague, took spatial audio recordings of the forest ambiance, and built the forest's digital twin in Unreal Engine. To compare the therapeutic efficacy of the virtual forest with its real counterpart, groups of volunteers spent half an hour in either the real forest, the virtual forest, or both. We collected 'participants' demographic and psychometric data, assessing their relaxation, emotional state, and cybersickness before and after the session. Our data show an increase in relaxation with no significant differences between the environments, although participants' emotional states did not improve in either condition. We found that participants' experiences were comparable between the environments, but cybersickness limited the potential efficacy of virtual forest bathing. The limitations of the virtual forests as a platform for research into forest bathing are discussed.